Anvisiki Gateway To Understanding The Hindu Knowledge Paradigm - Ni Kadek Surpi; Ni Nyoman Ayu Nikki Avalokitesvari (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
?nv?k?ik? science of inquiry has been recognized as a branch of learning in Hindu knowledge since 650 BCE. Medh?tithi Gautama is the Founder of ?nv?k?ik? par excellence, and this knowledge has continued to develop into the modern age while still having a strong function in building Hindu methods of knowledge. ?nv?k?ik? is the light of all knowledge. However, until now, it has not been widely studied in Hindu universities in Indonesia. Even though it is essential as a gateway to understanding the Hindu scientific paradigm, just as Hindu philosophy sharpens the machine of human intelligence, ?nv?k?ik? is a very sophisticated tool. This grinder sharpens intellect quickly and leads it to the development of logic and reason that is smooth and sharp. ?nv?k?ik? in its usable form also provides knowledge for discussion, debate, and as a critical study that helps in research and book writing.